Correlation of anaphylactic bronchoconstriction with circulating reaginic antibody level and active cutaneous anaphylaxis in the rat. - Church, M K (1975)
The interrelationships of anaphylactic bronchoconstriction, active cutaneous anaphylaxis and circulating reaginic antibody level in rats sensitized with Nippostrongylus brasiliensis have been studied. The mean rise in bronchial reactivity during the 5-week sensitization period was correlated with the rise in circulating reaginic antibody level in groups of rats, although weak bronchial reactivity was observed before circulating reagin was demonstrable. In individual animals bronchial reactivity did not significantly correlate with circulating reaginic antibody level or cutaneous reactivity. Bronchial and cutaneous reactivity on challenge may be transferred to non-sensitized rats by passive sensitization with reaginic serum. It is concluded that the ability of a tissue to respond to antigen challenge is multifactorial and may not be reliably predicted from a knowledge of circulating reaginic antibody level or the response of another tissue in the same animal.